2020
DOI: 10.4274/balkanmedj.galenos.2020.2020.7.52
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Management of Children With COVID-19 in Turkey

Abstract: Aims: Limited data about disease management strategies are available for pediatric patients with coronavirus disease-2019, particularly in Turkey. This study aimed to share the data on patients aged under 18 years in our country to be beneficial for understanding the disease course in children. Methods: A retrospective review of the medical records of pediatric patients aged under 18 years who were confirmed as coronavirus disease-2019 between March 11, and June 23, 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
64
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 24 publications
7
64
2
1
Order By: Relevance
“…The emerging infection due to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), named COVID-19, commonly has led a mild upper respiratory illness in children [ 1 4 ]. For instance, a study of 220 children with confirmed COVID-19 from Turkey, including our hospital, reported that 66% of cases presented with an asymptomatic and mild disease course, whereas 2.7% of the pediatric cases had a severe disease [ 5 ]. In the beginning of May 2020, a report of eight pediatric cases with a severe hyperinflammation as well as the involvement of several organs was published from London [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The emerging infection due to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), named COVID-19, commonly has led a mild upper respiratory illness in children [ 1 4 ]. For instance, a study of 220 children with confirmed COVID-19 from Turkey, including our hospital, reported that 66% of cases presented with an asymptomatic and mild disease course, whereas 2.7% of the pediatric cases had a severe disease [ 5 ]. In the beginning of May 2020, a report of eight pediatric cases with a severe hyperinflammation as well as the involvement of several organs was published from London [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been considered that bacterial infections in some of our suspected patients can be the reason for higher mean values of CRP and PCT than confirmed COVID‐19 patients. In Turkey, Cura et al 26 evaluated 220 pediatric COVID‐19 cases and reported that 17.8% of patients had increased CRP, 2.3% increased PCT, 8.4% neutropenia, 13.5% lymphopenia, and 0.9% had thrombocytopenia. In our study, 14.3% of confirmed COVID‐19 patients had neutropenia, 25.9% patients lymphopenia, and 4.4% thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…The large pediatric series from China showed that only 0.6% of the patients progressed to ARDS or multiple organ dysfunction (4) . In two pediatric studies from Turkey, dyspnea or tachypnea were observed less than 5% of the patients (18,19) . Similarly, the majority of our patients (81%) had mild disease.…”
Section: Discussionmentioning
confidence: 94%
“…In Turkey, schools were closed immediately after the detection of the first case in the country, and home isolation for children had been implemented starting from the beginning of the outbreak. In different pediatric studies reported from Turkey, exposure has been reported in 90-99% (18,19) . Similarly, in our case series, the source of infection in almost all children with COVID-19 was a household member or an immediate family mem- ber.…”
Section: Discussionmentioning
confidence: 99%